The Influence of Motivation and Work Environment on Employee Performance at Batam's Hang Nadim International Airport - Indira Tasya Afifa; You She Melly Anne Dharasta (International Journal of Management Science, 2023)
Batam Hang Nadim International Airport is an international airport located in Batam City, Riau Archipelago. Currently managed by PT.BIB which houses 3 large companies, each company brings the best employees to achieve common goals. To achieve this company's goals, good employee performance is needed, many factors can influence this, namely motivation and work environment. The research design in this study is a quantitative study. This research method is a type of research whose specifications are systematic, structured and clearly planned from the start. This study aims to determine the effect of motivation and work environment on employee performance at Batam's Hang Nadim International Airport. With data collected by distributing questionnaires, namely 90 respondents who work at Hang Nadim International Airport, so it can be concluded that motivation and work environment affect the performance of employees at Hang Nadim airport, Batam. This is evidenced by the results of the f test obtaining a significance value of 0.000 less than 0.05 and R Square or the coefficient of determination Motivation and Work Environment together contribute to the influence of Employee Performance by 64.3% and the remaining 35.7% employee performance influenced by other variables not examined in this study.